Encephalopathy in COVID-19 Presenting With Acute Aphasia Mimicking Stroke - Pensato, Umberto (Front Neurol, 2020)
Introduction: Neurological manifestations are emerging as relatively frequent complications of corona virus disease 2019 (COVID-19), including stroke and encephalopathy. Clinical characteristics of the latter are heterogeneous and not yet fully elucidated, while the pathogenesis appears related to neuroinflammation in a subset of patients. Case: A middle-aged man presented with acute language disturbance at the emergency department. Examination revealed expressive aphasia, mild ideomotor slowing, and severe hypocapnic hypoxemia. Multimodal CT assessment and electroencephalogram (EEG) did not reveal any abnormalities. COVID-19 was diagnosed based on chest CT findings and positive severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) reverse transcription PCR (RT-PCR) on nasopharyngeal swab. The following day, neurological symptoms progressed to agitated delirium and respiratory status worsened, requiring admission to the ICU and mechanical ventilation. Brain MRI and cerebrospinal fluid (CSF) studies were unremarkable. RT-PCR for SARS-CoV-2 on CSF was negative. He received supportive treatment and intravenous low-dose steroids. His neurological and respiratory status resolved completely within 2 weeks. Conclusions: We report a patient with reversible COVID-19-related encephalopathy presenting as acute aphasia, mimicking stroke or status epilepticus, eventually evolving into delirium. Although large-vessel stroke is frequently encountered in COVID-19, our case suggests that focal neurological deficits may occur as the earliest feature of encephalopathy. Neurological status reversibility and the absence of abnormalities on brain MRI are consistent with a functional rather than a structural neuronal network impairment.